ANALISIS CUSTOMER SATISFACTION PADA TRANSPORTASI ONLINE BERBASIS ANDROID DENGAN MENGGUNAKAN METODE BLACKBOX CUSTOMER - Novita, Diana; Yuliani, Nafisah (Fakultas Teknik Universitas Persada Indonesia YAI, 2019)
Online transportation now becoming more popular than the confessionals one. People nowadays are likely to use the online transportation comparing using the old fashion models of transportation. Specially in big city like Jakarta, where the mobility of the people are huge. As we know that there are three online transportation company in our beloved city, Jakarta. Those three company off course has their own unique way on treating the customers. Because of all those variaty, customers sometimes having difficulty on choosing their own favorite online transportation. As also we know, these online transportations can be use online with specific device, hat is a smartphone which runs in android operationg systems. That means, that we canât use the online transportations using our laptop or personal computers. Smartphone based on android is one of the famouse device that many people use in their daily life. Smartphone is really userfrindly and easy to use, thats why many pople usually says about this device and thats what makes smartphone become famouse device nowadays. By using the smartphone, our many routine jobs can be do easily with it. Including booked an online transportation services. A company who runs in a services field, should be very needed for the good resources specially human resources, in order to give a best services for their customers. Thats why, the company should be very selective on choosing the resources. The varieties of the customers should maintain very well by each online transportation company because every customers has their own standaritations of satisfactions. Based on the questionairs, the main point to calculate the satisfaction of the customers start from the human resources that directly interact with the customers, in these case, is a driver who work for the company. The increasing of the quality and sercices that driver gives, are really decide the customers satisfactions. So, the company should held some trainings for the drivers in order to give the best services for the customers. But the main problem now is how can we choose the best online transportation to be our partner in doing our routine activites ? thats what we are going to find out using blackbox customers method.